Gest??o de projetos e a internacionaliza????o de empresas brasileiras: um estudo sob a perspectiva da RBV - Schelini, Andr?? Luiz Spinelli (2015)
Firms face challenges of various natures in different competitive environments, depending on the target market, the business model and corporate strategies. Operate in international markets is a constant challenge on the schedule of firms in the global environment to start their internationalization process. Are challenges since the capitalization of resources, new markets and customers, development of competencies and capabilities, directed to the strategic formation of the company's internationalization, among others. This study focuses on three theoretical areas: project management, internationalization of companies and the resource-based view (RBV). Thus defined the following research question: "How the project management maturity contributes to internationalization of Brazilian companies from the perspective of resource-based view???? Particularly analyzed the contributions of mature project management for internationalization features in international Brazilian companies from the RBV-VRIO analysis, ie, examined whether the mature nature of the management of projects adopted by the selected companies are considered strategic resources, with implications competitive, sustainable competitive advantage for the company. The research strategy adopted was a multiple case study of descriptive exploratory approach within-case analysis and cross-case method, in internationalized Brazilian companies from different business segments. As a result, the study found that the project management features: sustainability of the project, involvement of stakeholders, defining objectives and strategies, change management and risk management, have the greatest contribution to the internationalization of selected companies, with implication of competitive advantage sustainable, considering the RBV-VRIO analysis. Thus, the research presents contributions for companies that are or intend to initiate a process of internationalization, so the process is clearer and driven to a better use of market opportunities.